Human β-Defensin 2 Mediated Immune Modulation as Treatment for Experimental Colitis - Koeninger, Louis; Armbruster, Nicole S.; Brinch, Karoline Sidelmann; Kjaerulf, Søren; Andersen, Birgitte; Langnau, Carolin; Autenrieth, Stella E.; Schneidawind, Dominik; Stange, Eduard F.; Malek, Nisar P.; Nordkild, Peter; Jensen, Benjamin A. H.; et al. (Frontiers in Immunology, 2020)
Defensins represents an integral part of the innate immune system serving to ward off potential pathogens and to protect the intestinal barrier from microbial encroachment. In addition to their antimicrobial activities, defensins in general, and human β-defensin 2 (hBD2) in particular, also exhibit immunomodulatory capabilities. In this report, we assessed the therapeutic efficacy of systemically administered recombinant hBD2 to ameliorate intestinal inflammation in three distinct animal models of inflammatory bowel disease; i.e. chemically induced mucosal injury (DSS), loss of mucosal tolerance (TNBS) and T-cell transfer into immunodeficient recipient mice. Treatment efficacy was confirmed in all tested models, where systemically administered hBD2 mitigated inflammation, improved disease activity index and hindered colitis-induced body weight loss on par with anti-TNF-α and steroids. Treatment of lipopolysaccharide (LPS)-activated human peripheral blood mononuclear cells with rhBD2 confirmed the immunomodulatory capacity in the circulatory compartment. Subsequent analyzes revealed dendritic cells (DCs) as the main target population. Suppression of LPS-induced inflammation was dependent on chemokine receptor 2 (CCR2) expression. Mechanistically, hBD2 engaged with CCR2 on its DC target cell to decrease NF-κB and increase CREB phosphorylation, hence curbing inflammation. To our knowledge, this is the first study showing in vivo efficacy of a systemically administered defensin in experimental disease.